The impact of Tai Chi’s “Xuling Dingjin” posture on lumbar biomechanics during stair descent - Duan, Yiting; Liu, Haibin; Jiang, Jian; Liu, Liqing; Gao, Fan; Li, Suheng; Yang, Yulong; Yang, Shuye; Yan, Shudong (Frontiers in Sports and Active Living, 2025)
BackgroundLow back pain is common increases stair-related fall. The Tai Chi “Xuling Dingjin” posture may enhance spinal stability, its biomechanical mechanisms remain unclear. This study investigates the effects of this posture on lumbar biomechanics during stair descent, and provides theoretical support for its application in balance improvement and rehabilitation.Research questionTo investigate the biomechanical effects of Tai Chi's “Xuling Dingjin” posture on the lumbar spine and whether it enhances the stability of the lumbar spine in the staircase environment.MethodsTwelve adults (6 males and 6 females) with a minimum of 5 years of Tai Chi experience participated in the study. Lumbar biomechanics were assessed during normal stair descent (D) and stair descent incorporating the “Xuling Dingjin” posture (XD) using a Vicon motion capture system, an AMTI force platform, OpenSim biomechanical analysis software, and finite element analysis.ResultsUnder the XD condition, deep stabilizing muscles (especially quadratus lumborum) exhibited earlier and more intense activation. Additionally, there was a smaller offset between the center of mass (COM) and center of pressure (COP), indicating improved posture stability. Lumbar rotation around the Z-axis was significantly decreased, and finite element analysis demonstrated a more uniform pressure distribution across the intervertebral discs.ConclusionMaintaining the “Xuling Dingjin” posture can activate deep stabilizers earlier and more effectively, redistributing lumbar pressure through postural adjustment, thereby enhancing spinal stability and offering potential value in reducing fall risk.